Exploring and expanding the spaces between research and implementation in conservation science. (December 2019) - Maas, Bea; Toomey, Anne; Loyola, Rafael
Abstract: Despite increased focus on the importance of navigating the spaces between research and implementation, conservation science is still not put into practice as often as it could be. Disciplinary and geographical biases, as well as insufficient funding or recognition of interdisciplinary communication, limit engagement between scientists, practitioners and decision-makers in the field of conservation science - especially in early stages and the follow-up of conservation projects. In light of the current global biodiversity and climate crisis, the broad community of conservation science faces questions with regard to how we can explore and expand implementation spaces to create opportunities for better collaboration and communication between science and our society: (1) Do we have our priorities right? (2) Are we documenting and learning from our successes and failures through evaluation? (3) And who are we including or excluding in the spaces between research and implementation? In this editorial, we present an overview of our Special Issue on "Implementation Spaces in Conservation Science", in which these questions and the challenges that they raise are highlighted. Finally, we ask whether conservation science is ready for a paradigm shift - not only in the ways we do conservation, but also in how we think about it. This shift would open new avenues towards modern ways of implementing conservation evidence into practice through teaching, training and evaluation integrated into cooperation and communication with other disciplines and non-scientists. Ultimately, it will help us to properly measure success and thus influence cooperation with policy and decision-makers in conservation, but also promote integration of more diverse perspectives and knowledges from yet underrepresented parts of the conservation science landscape.